2011
DOI: 10.1007/s00044-011-9623-3
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and biological evaluation of novel 2,4-thiazolidinedione derivatives as histone deacetylase inhibitors targeting liver cancer cell line

Abstract: As a part of an ongoing effort to find alternate chemotherapeutic agents for hepatocellular carcinoma, we herein, report the design and synthesis of two novel compounds targeting histone deacetylase (HDAC) with 2,4-thiazolidinedione as zinc chelating group. Further, we demonstrate that these compounds show cytotoxicity that parallels their ability to inhibit HDACs activity in human liver cancer cell line HepG2. The findings obtained in this study indicate that 2,4-thiazolidinedione group may be utilized succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 19 publications
(16 reference statements)
0
25
1
Order By: Relevance
“…We have reported anti-diabetic [11], histone deacetylase (HDAC) inhibitory potential [17] of our synthesized TZD molecules. Recently we reported VEGFR-2 inhibitory activity of 5-pyridin-4-yl-2-thioxo-1,3,4-oxadiazole derivatives [18].…”
Section: Resultsmentioning
confidence: 98%
“…We have reported anti-diabetic [11], histone deacetylase (HDAC) inhibitory potential [17] of our synthesized TZD molecules. Recently we reported VEGFR-2 inhibitory activity of 5-pyridin-4-yl-2-thioxo-1,3,4-oxadiazole derivatives [18].…”
Section: Resultsmentioning
confidence: 98%
“…It is a bioisosterical form of 1,3-thiazolidine-2,4-dione which has been shown to have good inhibitory activity against HDAC Zn 2+ cofactor in liver cancer cell lines (Mohan et al, 2011). As a linker, paraaminobenzoic acid (PABA) was chosen as it has been shown to have strong interaction with hydrophobic residues on HDAC cylindrical pocket.…”
Section: Hdac Inhibitor (Hdaci) Ligands Designmentioning
confidence: 99%
“…Based on pharmacophore modeling, a good HDAC inhibitor has at least three sides/regions: the attachment side of the Zn 2+ cofactor/HDAC active site (Zn 2+ binding group/ZBG), hydrophobic cap (CAP) and linker containing connecting unit (CU) with electronegative groups (Mohan et al, 2011;Rossi et al, 2011). In this study, the novel HDAC inhibitors (HDACIs) were designed from 2-oxo-1,3-thiazolidine as Zn 2+ binding group/ZBG, para-amino benzoic acid (PABA) as linker and acetamide as connecting unit (CU) on hydrophobic cap (CAP) (Marek et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, one possible mechanism of cytotoxicity could be nucleophilic alkylation at the b position. Recently Mohan et al (2012) demonstrated that several thiazolidine-2,4-dione compounds also exhibited histone deacetylase inhibition effects. Encouraged by this finding, we evaluated the effects of six compounds including 4a-f on histone deacetylation using a Western blot analysis.…”
Section: Bioactivitymentioning
confidence: 99%
“…1) act as potent ligands of PPAR-c and show efficient insulin sensitization in type 2 diabetes patients (Bhattarai et al, 2010;Patel et al, 1999). Recently, a number of thiazolidine-2,4-dione incorporating compounds were also reported to be potent protein tyrosine phosphatase 1B (PTP1B) inhibitors (Bhattarai et al, 2010;Maccari et al, 2007), and in particular, some thiazolidinediones were also demonstrated to have histone deacetylase inhibitory effects (Mohan et al, 2012) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%